Annual Report on Exchange Arrangements and Exchange Restrictions 2019. (Annual Report on Exchange Arrangements and Exchange Restrictions, 2020)
The Annual Report on Exchange Arrangements and Exchange Restrictions has been published by the IMF since 1950. It draws on information available to the IMF from a number of sources, including that provided in the course of official staff visits to member countries, and has been prepared in close consultation with national authorities.